The nature and impact of occupational trauma exposure among staff working in a forensic medical and scientific service: a qualitative interview study. Issue 2 (4th March 2023) - Wayland, S.; Cook, O.; Cartwright, A.; Ryan, J.; Brondolo, E.; Bassed, R.; Bugeja, L.
ABSTRACT: Employees of forensic medical service organizations are exposed to occupational trauma during their clinical, pathology, scientific and corporate duties. Adverse impacts, associated with occupational trauma exposure, can illicit negative outcomes that may influence a person's professional practice as well as their physical, behavioural and psychological reactions. Research exploring the impact of trauma exposure has typically focused on reduction of exposure, failing to address workplaces where exposure to trauma is a core activity for employees. This study explored the experiences of staff working at a state-wide forensic medical and scientific institution in Australia. Thematic analysis of 25 key-informant interviews identified that 1) trauma exposure is common and multifactorial in nature; 2) impacts of trauma exposure varies by personal characteristics and case circumstances; and 3) trauma exposure can be better managed when organizational and individual responsibility align. Awareness that a strong sense of purpose and contribution derived from the important nature of the work delivered, allows individuals to remain employed. The study also identified that facilitating a culture of openness regarding trauma exposure can lead to improved workplace wellbeing and retention of this dedicated workforce.